Analysis of ethical decisions of tax consultants in Southern Sumatra Region - Wiwik Tiswiyanti; Haryadi Haryadi; Sri Rahayu; Enggar Diah Puspa Arum (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
This study aims to determine the factors that influence the ethical decision-making of tax consultants in the Southern Sumatra Region. The population of this research is all tax consultants who are members of the Indonesian Tax Consultants Association (IKPI), which includes the provinces of Lampung, South Sumatra, Bangka Belitung, and Jambi. The total population is 139 tax consultants. The entire population was used as the research sample (with a return sample of 109 respondents). Data were analyzed using SEM-WarpPLS. The results of the analysis found that: (1) Machiavellian had a negative effect on ethical decisions (2) Machiavellian had a negative effect on ethics and social responsibility (3) Ethics and social responsibility had a positive effect on ethical decisions (4) Ethics and social responsibility can partially mediate the relationship between Machiavellian and ethical decisions